2017
DOI: 10.4103/2045-9912.202904
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training provides cardioprotection by activating and coupling endothelial nitric oxide synthaseviaa β3-adrenergic receptor-AMP-activated protein kinase signaling pathway

Abstract: Exercise training confers sustainable protection against ischemia/reperfusion injury. However, the mechanism by which this process occurs is not fully understood. Previously, it was shown that β3-adrenergic receptors (β3-ARs) play a critical role in regulating the activation of endothelial nitric oxide synthase (eNOS) in response to exercise and play a critical role in exercise-mediated cardioprotection. Intriguingly, a deficiency in β3-ARs led to increased myocardial injury following exercise training. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Fang et al 20) confirmed that nebivolol treatment improved left ventricular diastolic function via enhancement of NO bio-availability and was completely abolished by the NO synthase inhibitor N ω -Nitro-L-arginine (L-NNA). Zhang et al 37) also reported the cardio-protective effects of nebivolol could be abolished by the β 3 -adrenoceptor antagonist SR59230A. Barr et al 38) reported that due to increases in superoxide levels through eNOS uncoupling, exercise could increase the size of the myocardial infarction area in β 3 -adrenoceptor knockout mice, and treatment with BH4 significantly reduced this myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al 20) confirmed that nebivolol treatment improved left ventricular diastolic function via enhancement of NO bio-availability and was completely abolished by the NO synthase inhibitor N ω -Nitro-L-arginine (L-NNA). Zhang et al 37) also reported the cardio-protective effects of nebivolol could be abolished by the β 3 -adrenoceptor antagonist SR59230A. Barr et al 38) reported that due to increases in superoxide levels through eNOS uncoupling, exercise could increase the size of the myocardial infarction area in β 3 -adrenoceptor knockout mice, and treatment with BH4 significantly reduced this myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation of rat aortic rings caused by SR 58611A was sensitive to K Ca , K v and K ATP inhibitors (Rautureau et al, 2002). Cardiovascular endothelial β 3 -adrenoceptors have been linked to eNOS activation and EDH of vascular smooth muscle, with the reported mechanisms of NOS/EDH activation uncertain (Barr et al, 2017;Dessy et al, 2004;Kou & Michel, 2007;L.Y. Michel & Balligand, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In general, β 3 -adrenoceptors are established as G s -coupled receptors stimulating adenylate cyclase/cAMP accumulation (Dessy & Balligand, 2010;, but this mechanism was not involved in the β 3 -adrenoceptor-mediated responses observed in the present study as the PKA-inhibitor peptide enhanced, rather than inhibited responses. Possible alternative β 3 -adrenoceptor signalling pathways include eNOS phosphorylation by AMP-kinase (Barr et al, 2017) with a potential role for Rac1 (Kou & Michel, 2007), and caveolae and the associated proteins, caveolin-1 and caveolin-3 (Belge et al, 2014;Sato et al, 2012). The role of K Ca 3.1 in endothelial β 3 -adrenoceptor-mediated (as opposed to isoprenaline-mediated) responses suggests elevation of endothelial intracellular [Ca 2+ ] is also a contributing factor (Murphy & Sandow, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms converge in multiple kinase cascades that stimulates eNOS activity and increase generation of NO by shear stress, due to increased blood flow as a product of exercise ( Adams et al, 2017 ). In addition, exercise can reduce the myocardial infarct size after in vivo I/R injury by increasing eNOS activity and coupling, which in turn is mediated by a β3-adrenergic receptor/AMP-activated protein kinase signaling pathway ( Barr et al, 2017 ). However, another study showed that exercise protects the myocardium from MI in obese and diabetic mice, but while this effect was associated with reduced inducible nitric oxide synthase (iNOS), it was independent of β3-adrenergic receptor ( Kleindienst et al, 2016 ), suggesting that exercise-induced cardioprotection is a complex phenomenon and much research needs to be performed to altogether remove the veil covering pro-survival pathways in different physiological or pathophysiological contexts.…”
Section: New Insights Of Endothelial-mediated Protection Against Ischmentioning
confidence: 99%